Digital technology to facilitate Proactive Assessment of Obesity Risk during Infancy (ProAsk): a feasibility study - Redsell, Sarah A.; Rose, Jennie; Weng, Stephen; Ablewhite, Joanne; Swift, Judy A.; Siriwardena, Aloysius Niroshan; Nathan, Dilip; Wharrad, Heather J.; Atkinson, Pippa; Watson, Vicky; McMaster, Fiona; Lakshman, Rajalakshmi; et al. (BMJ Publishing Group Ltd, 2017)
Objective: To assess the feasibility and acceptability of using digital technology for Proactive Assessment of Obesity Risk during Infancy (ProAsk) with the UK health visitors (HVs) and parents.